2017
DOI: 10.1108/ccsm-08-2016-0157
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of rules, asymmetries in language fluency, and team dynamics in culturally diverse teams

Abstract: Purpose -The purpose of this paper is to explore how newly formed culturally diverse project teams develop and implement rules, and how these processes may be affected by language-fluency asymmetries. Design/methodology/approach -Using a case-study research design, the authors investigated three multicultural project teams within a management integration program in a multinational company in France. Their complete data set includes 37.5 hours of observations and 49 hours of semi-structured interviews. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Cultural diversity in teams is associated with an increase in social stressors within teams. While tensions can occur in different types of teams, cultural diversity among team members amplifies individual differences, which can result in an increase in disagreements, misunderstandings, conflicts and distrust (Harush et al , 2018; Henderson, 2005; Leifels, 2020; Pines and Zaidman, 2014; Stahl et al , 2010; Williams and O'Reilly, 1998; Vigier and Spencer-Oatey, 2018).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural diversity in teams is associated with an increase in social stressors within teams. While tensions can occur in different types of teams, cultural diversity among team members amplifies individual differences, which can result in an increase in disagreements, misunderstandings, conflicts and distrust (Harush et al , 2018; Henderson, 2005; Leifels, 2020; Pines and Zaidman, 2014; Stahl et al , 2010; Williams and O'Reilly, 1998; Vigier and Spencer-Oatey, 2018).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…With increasing globalization, the prevalence of multicultural work teams in organizations has grown (Haas and Nüesch, 2012; Vihgier and Spencer-Oatey, 2018). Cultural diversity in work teams is associated with considerable positive potential, as the different backgrounds and experiences of members can be a competitive advantage (Cox and Blake, 1991; Engelhard and Holtbrügge, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vigier and Spencer- Oatey (2018), in a study of French and English speaking teams who worked for a French-based multinational company, found that team members formed subgroups on the basis of fluency in the working language of the team. Moreover, when other variables, notably professional sector, gender and age, were also aligned with the language fluency faultline, the fractures were very sharp and deep and difficult to overcome.…”
Section: Identity Faultlines and Team Cohesion/divisionsmentioning
confidence: 99%
“…• Case studies of successful team working so that we can gain a richer picture of the bright side of multicultural team working (Stahl, Mäkela, et al, 2010); • Longitudinal case studies of multicultural teams so that we can gain insights into developments in team relations over time (Debray & Spencer-Oatey, 2019); • Discourse-based studies of multicultural teams so that we can gain a deeper understanding of the ways in which team members use cultural identity as a way of positioning themselves and each other (Barinaga, 2007); • Longitudinal, observational/discourse-based studies of multicultural teams so that we can gain insights into helpful and less helpful interactional strategies (DiStefano & Maznevski, 2000;Vigier & Spencer-Oatey, 2018); • Greater use of digital research methodologies, such as social network analysis, so that we can gain greater insights into issues such as member identification or communication and trust (Sarker, Ahuja, Sarker, & Kirkeby, 2011) As Jonsen et al (2012, p. 387) point out, "Only to the extent that we can explore questions like these, will we be able to provide guidance to organizations to help them prepare for the future."…”
Section: Future Directionsmentioning
confidence: 99%
“…It is well known that understanding of how processes are impacted by language and communication barriers across multicultural borders can improve the efficiency of the workplace (e.g. Vigier and Spencer-Oatley, 2018). The strategic role of multinationals should not be underestimated and the headquarters needs to have the best understanding of the operations in that development (Magomedova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%